TEACHING PRONUNCIATION IN ENGLISH LANGUAGE EDUCATION: AN ACADEMIC PERSPECTIVE - Abdurahmonova Hayitgul,; Egamberdiyeva Hadicha,; Furqatova Bonu, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Pronunciation  is  a  fundamental  component  of  second  language  acquisition, particularly in English language teaching, where effective oral communication is a primary  goal.  Despite  its  significance,  pronunciation  has  historically  received  less attention  compared  to  grammar  and  vocabulary.  However,  contemporary  research highlights that systematic pronunciation instruction can significantly improve learners’ intelligibility and communicative competence (Celce-Murcia et al., 2010). The primary objective of teaching pronunciation is not to eliminate a learner’s accent,  but  to  ensure  intelligibility.  According  to  Derwing  and  Munro  (2005), intelligibility,  comprehensibility,  and  accentedness  are  separate  constructs. Intelligibility  refers  to  how  much  a  listener  understands,  while  comprehensibility concerns how easy the speech is to understand. Therefore, pronunciation instruction should prioritize features that most affect communication, such as stress, rhythm, and intonation, rather than aiming for native-like perfection. There  are  two  widely  recognized  approaches  to  teaching  pronunciation:  the intuitive-imitative  approach  and  the  analytic-linguistic  approach.  The  intuitive-imitative approach emphasizes listening and repetition, allowing learners to imitate native speaker models. This approach can be effective in immersive environments. In contrast,  the  analytic-linguistic  approach  involves  explicit  instruction  in  phonetic features, including the use of phonemic symbols and articulatory explanations (Kelly, 2000).